2009
DOI: 10.1007/s00432-009-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Transformation potential of bone marrow stromal cells into undifferentiated high-grade pleomorphic sarcoma

Abstract: The present study suggests that UHGPSs are derived from BM stromal cells, probably mesenchymal stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Interestingly, transformation of dermal MSC resulted in formation of UPS, consistent with previous reports which used bone marrow MSC. 5,7 At the same time, Rodriguez et al 35 reported formation of fibrosarcomas with areas of adipose tissue differentiation after subcutaneous injection of MSC derived from adipose tissue of p21 Ϫ/Ϫ p53 Ϫ/Ϫ mice into immunodeficient mice. These variations in tumor type may reflect either different differentiation potential of MSC derived from different locations or gene-dependent differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, transformation of dermal MSC resulted in formation of UPS, consistent with previous reports which used bone marrow MSC. 5,7 At the same time, Rodriguez et al 35 reported formation of fibrosarcomas with areas of adipose tissue differentiation after subcutaneous injection of MSC derived from adipose tissue of p21 Ϫ/Ϫ p53 Ϫ/Ϫ mice into immunodeficient mice. These variations in tumor type may reflect either different differentiation potential of MSC derived from different locations or gene-dependent differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, formation of UPS was reported after transplantation of bone marrow-derived mouse MSC treated with 2-methylcholanthrene. 7 Intriguingly, it has been reported that according to cell lineage tracing experiments in irradiation chimeras, spontaneous fibrosarcomas arise from bone marrow-derived cells in the mouse. 74 To evaluate a possibility of bone marrow origin of STS in our model, we have performed irradiation chimera experiments in which donor and recipient cells carried floxed copies of p53 and Rb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcomas are relatively rare, and many types tend to occur in childhood and adolescents with poor prognosis. Most of sarcomas, probably not all, are considered to be originated from mesenchymal stem/progenitor cells (22), and there have been several reports indicating MSCs could transform some type of sarcoma cells (23)(24)(25). However, there have been few reports regarding the MSCs as tumor stroma in sarcoma tissues (26).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports indicate that sarcoma can evolve from murine MSC cultures (Li et al 2010 ;Tolar et al 2007 ) . Karnoub and coworkers demonstrated that bone-marrow-derived human mesenchymal stem cells, when mixed with otherwise weakly metastatic human breast carcinoma cells, cause the cancer cells to increase their metastatic potency greatly when this cell mixture is introduced into a subcutaneous site and allowed to form a tumour xenograft (Karnoub et al 2007 ) .…”
Section: Potential Applications For Therapiesmentioning
confidence: 99%